Pengaruh Audit Jarak Jauh (Remote Audit) dan Jumlah Penugasan Auditor terhadap Kualitas Audit: Studi Empiris pada Perwakilan BPKP Provinsi Sumatra Barat - Nurul Hanifah Putri; Erly Mulyani (Universitas Negeri Padang, 2022)
This study aims to provide empirical evidence regarding the effect of remote audits and the number of auditor assignments on audit quality. The research method was verifiable with a quantitative approach. This study used multiple linear regression analysis to test the proposed hypothesis. The population in this study was all auditors who worked in the BPKP Representative of West Sumatra Province, with a total of 95 auditors. The sampling technique in this study was saturated sampling or census, therefore, the total sample used in this study was the total population. The data source in this study wash the primary data source, which was obtained by distributing questionnaires directly to research respondents. The results of this study showed that remote audits had a significant positive effect on audit quality, and the number of auditor assignments did not have effect on audit quality. For further research, it is expected to be able to examine other dependent variables besides audit quality, such as auditor performance and is expected to be able to add research data collection methods as well as using interview methods.